2022
DOI: 10.1177/22125868211067288
|View full text |Cite
|
Sign up to set email alerts
|

Can managerialism promote organisational transformation in private universities?

Abstract: Used as a method of university reform, new public management (NPM) involves an ideology of managerialism that conflicts with collegiality and causes ‘hybridisation’. In management organisations, when organisational goals are not shared at the individual level, this adjustment mechanism shifts to the organisational level. This study aimed to examine whether there are coordination mechanisms at the organisational level in universities by focussing on those in Japan, particularly private universities that require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Similarly, Maeda [31] focused on the instrumental aspects of organizational culture using the CVF scale. This study conducted a quantitative study using a multilevel model on faculty members at a private universities and revealed the mechanisms that generate and suppress conflict as a factor of opportunistic behaviour and revealed the fact that an organizational culture that emphasises research reduces conflict, while an organizational culture that emphasises competition between universities and centralisation of power in the university executive reinforces conflict.…”
Section: Survey Of Previous Researchmentioning
confidence: 99%
“…Similarly, Maeda [31] focused on the instrumental aspects of organizational culture using the CVF scale. This study conducted a quantitative study using a multilevel model on faculty members at a private universities and revealed the mechanisms that generate and suppress conflict as a factor of opportunistic behaviour and revealed the fact that an organizational culture that emphasises research reduces conflict, while an organizational culture that emphasises competition between universities and centralisation of power in the university executive reinforces conflict.…”
Section: Survey Of Previous Researchmentioning
confidence: 99%
“…Taking a snapshot of 2022 papers reveals the quality and depth of scholarship being published. 10 articles were published between January and April (Aatif, 2022; Cui et al, 2022; Kazuyuki, 2022; Li and Longpradit, 2022; Nicol and Bice, 2022; Sung et al, 2022; Zhang, 2022; Zhao and Ebanda de B’beri, 2022; Zheng, 2022). Following a growing pattern, these articles were submitted to IJCE from researchers and authors without prior attachment to IJCE, IOE or Tsinghua.…”
Section: A Picture Of 2022 So Farmentioning
confidence: 99%